Crackle and fizz : essential communication and pitching skills for scientists - Van den Brul, Caroline; Rothwell, Nancy (London : Imperial College Press, 2014)
This book is for scientists and other experts who need to explain the significance and potential of their work to colleagues, committees, funding bodies or the general public. It details how to harness story-telling principles to make complex or technical contents easier to communicate and fulfilling for audiences. --
Your audience: the person or people whose full engagement you need -- Change and affect: gives communication its meaning and impact -- Lure: an enticement, usually with a bait, offering the promise of a reward -- World: the contextual space in which your narrative will unfold -- Character: You! - the Audience's guide, in search of a prize -- Big hook: a puzzle which drives the narrative -- Plot: the perilous journey to solve the puzzle and reach the prize -- Structure: making the whole more than the sum of its parts -- Make your pitch CRACKLE: how to persuade, to win support.
Includes bibliographical references (pages 187-193) and index.
Keywords: Communication in science; Science -- Vocational guidance